Exploring The Impact of Promotional Strategies on New Product Success in the FMCG Sector - Trihatmoko, R. Agus; Mulyani, Roch (LifeSciFi, 2025)
This study explores the impact of promotional strategies on the success of new products in the Fast-Moving Consumer Goods (FMCG) sector, with a particular focus on the dynamics between manufacturers, distributors, and wholesalers. As the FMCG market is characterized by intense competition and rapid product cycles, promotional strategies play a critical role in driving consumer demand, shaping brand image, and influencing market share. Despite extensive research on the broader marketing mix, limited attention has been given to the specific influence of promotional tactics on new product success within this sector. This research bridges that gap by analyzing how different promotional approaches, including Above-The-Line (ATL) and Below-The-Line (BTL) strategies, impact both immediate buyer responses and long-term product performance. The findings suggest that promotion not only directly influences product visibility and consumer loyalty but also shapes market competition and pricing strategies. Additionally, the study highlights the interplay between promotional strategies and the competitive environment, providing valuable insights into how marketers can optimize promotional efforts to foster sustainable market growth. By applying a relationship marketing theory framework, this research provides actionable recommendations for FMCG companies to refine their promotional strategies, ensuring both short-term sales success and long-term brand recognition.